Implementation of Artificial Intelligence in School Environment - Banerjee, Nandini; Rakshit, Susmita (Far Western Review, 2025)
The growth of Artificial Intelligence (AI) has revolutionized almost all avenues of human activity, from medicine and transportation to recreation and politics. The education is one of these fields. AI has promising opportunities with complicated challenges in education. This brief quantitative assessment builds participant-level data from group means and sample sizes to analyze stakeholder attitudes towards artificial intelligence in the school environment. Nineteen participants among four stakeholder groups (academicians, law personnel, expert engineers, and teachers) are represented by participant-level percentage scores of perceived benefit of artificial intelligence (0-100%). Descriptive statistics, a between-groups comparison and visualizations are showed. The results indicate an overall mean perceived benefit of 70.05% (SD = 14.76), with expert engineers standing above the other groups at mean 95.0%. Significant group differences are, therefore, represented by a one-way ANOVA (F(3,15) = 193.53, p < .001). The implementation which turns out to be interdisciplinary, implications of necessary and fruitful policy and obviously the pilot testing for beginning the research- all are considered carefully.